2008
DOI: 10.1111/j.1440-1738.2008.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Petrology of the Yugu peridotites in the Gyeonggi Massif, South Korea: Implications for its origin and hydration process

Abstract: Peridotites exposed in the Yugu area in the Gyeonggi Massif, South Korea, near the boundary with the Okcheon Belt, exhibit mylonitic to strongly porphyroclastic textures, and are mostly spinel lherzolites. Subordinate dunites, harzburgites, and websterites are associated with the lherzolites. Amphiboles, often zoned from hornblende in the core to tremolite in the rim, are found only as neoblasts. Porphyroclasts have recorded equilibrium temperatures of about 1000°C, whereas neoblasts denote lower temperatures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…Arai et al . (2008), in a recent study on Yugu peridotite in South Korea, demonstrated that shearing/suturing and water supply linked with cooling led to the production of anhydrous high-temperature pyroxene porphyroclasts and lower temperature neoclasts of hydrated amphiboles. The basic processes associated with the formation of diopsidites from PCSZ are similar to those discussed above; particularly the trace and rare earth elements features are comparable with those of diopsidite dykes in Oman ophiolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arai et al . (2008), in a recent study on Yugu peridotite in South Korea, demonstrated that shearing/suturing and water supply linked with cooling led to the production of anhydrous high-temperature pyroxene porphyroclasts and lower temperature neoclasts of hydrated amphiboles. The basic processes associated with the formation of diopsidites from PCSZ are similar to those discussed above; particularly the trace and rare earth elements features are comparable with those of diopsidite dykes in Oman ophiolites.…”
Section: Discussionmentioning
confidence: 99%
“…The diopsides are rich in Sr and LREEs, and depleted in Ti, Nb, Ta and Zr. Arai et al (2008), in a recent study on Yugu peridotite in South Korea, demonstrated that shearing/suturing and water supply linked with cooling led to the production of anhydrous hightemperature pyroxene porphyroclasts and lower temperature neoclasts of hydrated amphiboles. The early crystallization of mica, amphibole and titanite particularly rich in HFSEs might reduce their concentrations in the residual melt.…”
Section: C Role Of Subduction-derived Fluids In the Formation Of Dmentioning
confidence: 99%
“…Another source could also be the decomposition of water from previous serpentine formations. These processes likely occurred during the uplift of the ophiolite from the upper mantle to the surface (Arai et al, 2008). The absence of plagioclase in ultramafic rocks indicates that the uplift process of these ultramafic rocks occurred rapidly (Maulana et al, 2015).…”
Section: Petrogenesis Of Ultramafic Rocksmentioning
confidence: 99%
“…In this reaction between the percolating melts and the harzburgite matrix, an "enriched component" would be added at the base of the mantle wedge in a SSZ context and the initial LILE-LREE-enriched melts would then percolate up through the porous mantle on the way to the surface (e.g. Parkinson and Pearce, 1998;Arai et al, 2008). En-route, the melt would react with relatively "unmetasomatized" mantle and might lose incompatible elements to the peridotite matrix or wall rocks along their way.…”
Section: Accepted Manuscriptmentioning
confidence: 99%